Correlative light electron microscopy (CLEM) for tracking and imaging viral protein associated structures in cryo-immobilized cells - Santarella-Mellwig, Rachel; Haselmann, Uta; Bartenschlager, Ralf; Romero-Brey, Inés (JoVE. Video journal, 2018)
Due to its high resolution, electron microscopy (EM) is an indispensable tool for virologists. However, one of the main difficulties when analyzing virus-infected or transfected cells via EM are the low efficiencies of infection or transfection, hindering the examination of these cells. In order to overcome this difficulty, light microscopy (LM) can be performed first to allocate the subpopulation of infected or transfected cells. Thus, taking advantage of the use of fluorescent proteins (FPs) fused to viral proteins, LM is used here to record the positions of the "positive-transfected" cells, expressing a FP and growing on a support with an alphanumeric pattern. Subsequently, cells are further processed for EM via high pressure freezing (HPF), freeze substitution (FS) and resin embedding. The ultra-rapid freezing step ensures excellent membrane preservation of the selected cells that can then be analyzed at the ultrastructural level by transmission electron microscopy (TEM). Here, a step-by-step correlative light electron microscopy (CLEM) workflow is provided, describing sample preparation, imaging and correlation in detail. The experimental design can be also applied to address many cell biology questions.
Enthält auch eine Versuchsbeschreibung in Textform
Gesehen am 17.05.2019
Wissenschaftlicher Film. Deutschland. 2018
Keywords: Film